Sociolinguistics Oxford introductions to languadge study - Spolsky B.; Widdowson H. G. (Oxford New York Oxford University Press, 1998)
Sociolinguistics is the study of the different ways in which various groups of people use language. This book provides a brief yet comprehensive introduction to the field. It explores how sociolinguistics is linked to other disciplines such as history, politics and gender studies
Keywords: 811.111